CRITICAL THINKING ABILITY OF STUDENTS IN SOLVING ETHNOPHYSICS QUESTIONS - Awaliah, Nur; Martawijaya, M. A.; Subaer, Subaer (JURNAL NALAR PENDIDIKAN, 2024)
This quantitative descriptive study aims to determine students' critical thinking abilities in solving ethnophysics questions. The data obtained in this study are quantitative data analyzed using descriptive statistics. The sample in this study was 58 students. Based on the Gregory test, the validity value obtained was one based on the Gregory test requirements if Vc ≥ 0.75 or ≥ 75%, then it can be declared feasible, so it can be concluded that all critical thinking ability questions are feasible to use, while the reliability value obtained was 0.74 then it can be declared reliable. The instrument used to collect data is an essay test of 10 questions developed using critical thinking indicators, including interpretation, analysis, evaluation, and inference indicators. Based on research data, it was found that students' critical thinking abilities in solving econophysics questions were in the medium category, with an average of 25.53. Based on the analysis of each indicator, it was obtained that the highest indicator of students' critical thinking skills, with an average score of 7.72, was in the evaluation indicator, followed by the interpretation, inference, and analysis indicators.